1994
DOI: 10.1099/13500872-140-9-2451
|View full text |Cite
|
Sign up to set email alerts
|

The physiological function of periplasmic glucose oxidation in phosphate-limited chemostat cultures of Klebsiella pneumoniae NCTC 418

Abstract: Periplasmic oxidation of glucose into gluconate and 2-ketogluconate in Klebsiella pneumoniae occurs via glucose dehydrogenase (GDH) and gluconate dehydrogenase (GaDH), respectively. Since, as is shown here, in the presence of glucose, gluconate and 2-ketogluconate are not further metabolized intracellularly the physiological function of t h i s periplasmic route was studied. It was found that periplasmic oxidation of glucose could function as an alternative production route of ATP equivalents. Instantaneous ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…In some microorganisms, the phenomenon of phosphate-starvation-inducible gene expression involves specific phosphate regulated genes and several of these are also inducible by other stress conditions [37]. Therefore, P availability seems to play an important role in regulating PQQ-GDH expression in some bacteria [38][39][40] including B. tropica, as shown in this work.…”
Section: Discussionsupporting
confidence: 59%
“…In some microorganisms, the phenomenon of phosphate-starvation-inducible gene expression involves specific phosphate regulated genes and several of these are also inducible by other stress conditions [37]. Therefore, P availability seems to play an important role in regulating PQQ-GDH expression in some bacteria [38][39][40] including B. tropica, as shown in this work.…”
Section: Discussionsupporting
confidence: 59%
“…The exclusive upregulation of LamPUL1 and LamPUL2 with laminarin but not glucose indicated finetuned sensing of polymeric vs. monomeric glucose, comparable to Gramella forsetii [16]. In this context, only laminarin induced the upregulation of gene cluster Alt831_00338⎼47 (Table S3) encoding three xylose/glucose isomerases, two glucose oxidoreductases and a gluconate 2-dehydrogenase, suggesting that only polymeric glucose is partially channeled into oxidative degradation to generate additional reducing equivalents [88].…”
Section: Cellular Adaptations During Sequential Degradation Of Polysamentioning
confidence: 80%
“…Evaluation of a large number of samples from a wide range of soil types has shown that, in general, highly efficient PSB are Gram‐Negative and utilize the direct oxidation glucose pathway to produce gluconic and 2‐ketogluconic acids (Krishnaraj and Goldstein 2001). Conversion of glucose to gluconic acid is facilitated by pyrolloquinoline quinone‐dependent glucose dehydrogenase (PQQ‐GDH) and gluconic acid oxidation to 2‐ketogluconic takes place via the FAD‐linked gluconate dehydrogenase (GADH) (Buurman et al. 1994; Buch et al.…”
Section: Introductionmentioning
confidence: 99%